2019
DOI: 10.1080/07391102.2019.1647286
|View full text |Cite
|
Sign up to set email alerts
|

Contriving a chimeric polyvalent vaccine to prevent infections caused by herpes simplex virus (type-1 and type-2): an exploratory immunoinformatic approach

Abstract: Herpes simplex virus type 1 (HSV-1) and 2 (HSV-2) cause a variety of infections including oral-facial infections, genital herpes, herpes keratitis, cutaneous infection and so on. To date, FDA-approved licensed HSV vaccine is not available yet. Hence, the study was conducted to identify and characterize an effective epitope based polyvalent vaccine against both types of Herpes Simplex Virus through targeting six viral proteins. The selected proteins were retrieved from viralzone and assessed to design highly an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…The N and C terminal of flagellin protein, RS09 peptide were used as adjuvants (Negahdaripour et al 2017 ; Yazdani et al 2020 ). Pan DR epitope (PADRE) sequence was used to counter the problems caused by polymorphic HLA alleles and to improve the stability of the vaccine (Hasan et al 2019 ). To link the epitopes and adjuvants linker sequence GGS was used (Yazdani et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The N and C terminal of flagellin protein, RS09 peptide were used as adjuvants (Negahdaripour et al 2017 ; Yazdani et al 2020 ). Pan DR epitope (PADRE) sequence was used to counter the problems caused by polymorphic HLA alleles and to improve the stability of the vaccine (Hasan et al 2019 ). To link the epitopes and adjuvants linker sequence GGS was used (Yazdani et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several advantages help the researchers to select membrane proteins both as drug and vaccine candidates as their functions can be easily studied through computer-based approaches PLOS ONE than wet-lab process [89,108]. In this study, two vaccine targets, 'Sensor histidine protein kinase UhpB (Q87HJ8)' and 'Flagellar hook-associated protein (Q87JH9)' were selected after screening the novel outer-membrane proteins (25) based on their antigenicity score and human microbiome non-homology analysis (Table 6).…”
Section: Plos Onementioning
confidence: 99%
“…The final vaccine constructs were designed with the help of different adjuvants and amino acid linkers [84]. It has been reported that the PADRE sequence reduces the polymorphism of HLA molecules in the population [108,109]. Linkers in vaccines also enhanced the immunogenicity of the vaccines in previous studies [110,111].…”
Section: Plos Onementioning
confidence: 99%
“…Henceforth, in the current approach, we have checked the propensity of the multi-epitope vaccine construct of the Nipah virus and human TLR3 complex. This epitope-based vaccine development approach has been explored and proved to be promising in a number of diseases caused by viruses like Herpes simplex virus (Hasan et al, 2019;Kumar et al, 2019), Yellow Fever Virus (Tosta et al, 2019), SARS Coronavirus (Srivastava et al, 2019), Chikungunya (Bappy et al, 2020), Dengue (Sabetian, Nezafat, Dorosti, Zarei, & Ghasemi, 2019), Alkhurma hemorrhagic fever virus (Ul-Rahman & Shabbir, 2019), etc. as well as by other pathogens including Leishmania donovani (Khatoon et al, 2019), Elizabethkingia anophelis (Nain et al, 2019), Flavobacterium columnare (Bhattacharya et al, 2020), Bacillus anthracis (Gupta, Khatoon, Mishra, Verma, & Prajapati, 2019), Streptococcus pneumoniae (Dorosti et al, 2019), Helicobacter pylori (Pasala et al, 2019), etc.…”
Section: Introductionmentioning
confidence: 99%